A Citation Analysis about Scholarship on Zines - Anne Hays (Journal of Librarianship and Scholarly Communication, 2020)
INTRODUCTION Zine scholarship is a relatively new academic field that has emerged since the late 1990’s. Now that two decades have passed since the publication of Stephen Duncombe’s seminal text, Notes From Underground, it is possible to take a landscape view of how and why zine scholars have studied zines in peer-reviewed journal publications. Knowing how scholars have studied zines can teach us about how zines and zine culture have contributed to academic knowledge. We can also learn which subjects are understudied as zine scholars continue to investigate these curious ephemeral print objects. METHODS This study uses citation analysis to uncover how scholars have explored zines and zine culture as objects worthy of academic inquiry between the dates of 1990 and 2018. The purpose of this study is to examine whether (and how) zines have held influence as objects worthy of study over time, to determine which disciplines tend to treat zines as a valuable academic pursuit, and to reveal what subtopics those scholars tend to focus on. RESULTS& DISCUSSION This study analyzes 163 peer-reviewed articles published between 1990 and 2018, and finds that a) scholarly interest in zines has increased steadily and by 1,700% over 28 years; b) that scholars in the fields of Library Science, Education, Feminist Studies, and Media Studies are most likely to study zines; and c) that zine scholars pursue a wide and varied range of subtopics most prominently concentrated in “riot grrrl” studies, “collection development,” “music criticism,” and a suite of articles about aspects of art. More nuanced analysis based on discipline and subtopic are discussed in the findings. CONCLUSION This study makes clear that zines are influential and worthy objects of study, not just as a form of print media, but as educational and pedagogical tools in the classroom, as evidence of activism, political movements, third-wave feminism, cultural critiques, cultural movements, and much more. Future scholars may use this study to build upon more established topics as well as those that are understudied.